2022
DOI: 10.3390/cancers14174229
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Allogeneic Natural Killer Cells in Combination with Pembrolizumab in Patients with Chemotherapy-Refractory Biliary Tract Cancer: A Multicenter Open-Label Phase 1/2a Trial

Abstract: Background and Aim: This study investigated the administration of combination therapy, allogeneic natural killer (NK) cells and pembrolizumab in the treatment of advanced biliary tract cancer to determine the safety and tolerability (phase 1) and the efficacy and safety (phase 2a). Methods: Forty patients (phase 1, n = 6; phase 2a, n = 34) were enrolled between December 2019 and June 2021. The patients received highly activated allogeneic NK cells (“SMT-NK”) on weeks 1 and 2 and pembrolizumab on week 1. This 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Data from the 23 patients who can be obtained efficacy evaluation for highlight its therapeutic potential. 201 Meanwhile, ociperlimab, a TIGIT inhibitor, in combination with tislelizumab and GemCis, are being tested in an ongoing phase II trial (NCT05023109).…”
Section: Ici Combination Trialsmentioning
confidence: 99%
“…Data from the 23 patients who can be obtained efficacy evaluation for highlight its therapeutic potential. 201 Meanwhile, ociperlimab, a TIGIT inhibitor, in combination with tislelizumab and GemCis, are being tested in an ongoing phase II trial (NCT05023109).…”
Section: Ici Combination Trialsmentioning
confidence: 99%
“…A number of additional CAR-T trials for BTCs are currently open, targeting mesothelin (NCT05568680, NCT05373147, and NCT05779917), HER2 (NCT04650451 and NCT04660929), MUC1 (NCT03633773), GPC3 (NCT04951141), and CEA (NCT05415475). Beyond CAR-T therapy, a phase I/IIa trial (NCT03358849) studying allogeneic NK cells (SMT-NK) plus pembrolizumab in the second line for advanced/metastatic BTCs demonstrated an ORR of 17.4% in the full analysis and 50.0% in the per-protocol analysis [ 63 ]. A direct comparison of this combination approach to pembrolizumab monotherapy is planned.…”
Section: Immunotherapy In Advanced Biliary Tract Cancersmentioning
confidence: 99%
“…As aforementioned, increasing the number of NK cells can inhibit tumor growth. A phase 1/2a trial explored the safety and efficacy of pembrolizumab combining allogeneic NK cells in chemotherapy-refractory BTC patients ( 158 ). That study reported an overall ORR and DCR of 17.4 and 30.4%, all without severe TRAEs.…”
Section: Immunotherapy For Cholangiocarcinomamentioning
confidence: 99%
“…That study reported an overall ORR and DCR of 17.4 and 30.4%, all without severe TRAEs. That study demonstrated that pembrolizumab plus allogeneic NK cells represents a promising therapeutic approach, exhibiting an improved efficacy and a favorable safety profile ( 158 ).…”
Section: Immunotherapy For Cholangiocarcinomamentioning
confidence: 99%